Answer:
Explanation:
We can write the given expression as :
As given, f = ∇f.
∇f =
+
+
We can write the partial derivative with respect to x, y and z.
___(Equation 1)
______(Equation 2)
______(Equation 3)
Take equation 2 and integrate with respect to y,
----------Equation 4
Derivate both sides w.r.t x , we get :
or
integrate
a(x,z)=b(z)
put in equation 4 ,
we get :
take derivative wrt z
we can take here:
integrate:
b(z) = C
The function can be written as :
from equation 4 :
Where C is a constant.